ACTION OF INDOLEACETIC ACID AND OF MONOPHOSPHATE 1 OF GLUCOSE ON GROWTH IN VITRO OF CORN ROOTS - BALDOVINOS DE LA PENA, GABRIEL (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1942)
Sections of 2 mm of apical meristem of primary roots, suspended for 24 hrs in concn of 1 x 10-6 [image] of indoleacetic acid, registered a retardation of growth, whereas in solns of 1 x 10-9 [image] they increased in length, fresh wt, and alcohol-ins
REV SOC MEX HIST NAT
Keywords: ACTION, INDOLEACETIC ACID, MONOPHOSPHATE1, GLUCOSE ON GROWTH, IN VITRO, CORN ROOTS; CIENCIAS DE LA VIDA; BIOLOGIA VEGETAL (BOTANICA); FISIOLOGIA VEGETAL